Perintisan Pelayanan Kelompok Sel di Gereja Bandung City Blessing Petra - Ferry Simanjuntak; Ana Ariesanita; Hana Venturini; Ernavina Pelmelay; Hana Yolanda (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2022)
Abstract Church planting cannot be separated from mission, because a church can be said to develop and grow if the church carries out a mission. Church activities that were hampered because of the pandemic did not hinder the spirit of God's church as the "called out" to carry out the fellowship of believers. During a pandemic, cell communities are formed by targeting young school-age children who are equipped to reach their environment. Through the zoom meeting, several activities were held aimed at increasing the understanding of cell community participants on God's word, the growth and maturity of members is also the target of this church planting. Keywords: church planting, cell communities, mission